Kūrish-i Kabīr : avvalīn āzādīkhvāh-i tārīkh-i jahān dar ā̲sār-i hunarī-i Urūpāʻīyāh - Humāyūn, Ghulām Alī (Intishārāt-i Dānishgāh-i Millī-i Īrān ; no.76., 1976)
On the life and accomplishments of Cyrus, King of Persia, d. 529 B.C., as portrayed in European art and literature.